Trustworthy computing : - Sahinoglu, Mehmet (Wiley-Interscience, 2007)
Trustworthy Computing: Analytical and Quantitative Engineering Evaluation presents an index-based, quantitative approach to advances in reliability and security engineering. Objective, metric-oriented, and data-driven, its goal is to establish metrics to quantify risk and mitigate risk through risk management. Complete with a CD-ROM containing case histories and projects that give readers hands-on experience, this is a great text for students in courses on security, reliability, and trustworthiness, as well as a reference for practicing software designers and developers, computer reliability and security specialists, and network administrators who work with data.